Handbook of Direct Democracy in Central and Eastern Europe after 1989 - Marczewska-Rytko, Maria (Verlag Barbara Budrich, 2018)
Since the collapse of the Soviet Union the political history of Central and Eastern Europe has been mainly the story of arise, consolidation, transformation and struggles of new democratic regimes and societies. The handbook offers an instructive approach to that history focusing on the relevance of practices and institutions of direct democracy. It collects 20 political analyses of direct democracy in 20 Central and Eastern European countries after 1989.